THE CONCEPT OF DIPLOMACY AND ITS HISTORICAL DEVELOPMENT - Ergasheva Feruzabonu Odiljonovna (TADQIQOTLAR.UZ, 2025)
Diplomacy,  the  art  and  practice  of  conducting  negotiations  between representatives  of  states,  is  a  cornerstone  of  international  relations.  Its  evolution reflects  the  complexities  of  human  interaction  and  the  shifting  dynamics  of  power across centuries. This article explores the historical development of diplomacy, from its ancient roots to its modern manifestations.